2016
DOI: 10.7150/ijbs.16134
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Growth Factors, But Not VEGF, Stimulate Glycosaminoglycan Hyperelongation in Retinal Choroidal Endothelial Cells

Abstract: A major feature of early age-related macular degeneration (AMD) is the thickening of Bruch's membrane in the retina and an alteration in its composition with increased lipid deposition. In certain pathological conditions proteoglycans are responsible for lipid retention in tissues. Growth factors are known to increase the length of glycosaminoglycan chains and this can lead to a large increase in the interaction between proteoglycans and lipids. Using choroidal endothelial cells, we investigated the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…GAG synthesizing enzymes (C4ST-1, ChSy-1 and XT-1) are responsible for sulfation and GAG chain (hyper) elongation; multiple other hormones and growth factors stimulate GAG elongation Getachew et al, 2010). In many studies, Vascular Endothelial Growth Factor (VEGF) stimulates GAG elongation but not in retinal endothelial cells (Al Gwairi et al, 2016). As to the in vivo relevance of these findings, Emoto and colleagues have shown that the mRNA expression of some GAG synthesizing genes increases over 8 weeks in an atherosclerotic mouse model and this increase correlates with increased atherosclerosis in the mice (Anggraeni et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…GAG synthesizing enzymes (C4ST-1, ChSy-1 and XT-1) are responsible for sulfation and GAG chain (hyper) elongation; multiple other hormones and growth factors stimulate GAG elongation Getachew et al, 2010). In many studies, Vascular Endothelial Growth Factor (VEGF) stimulates GAG elongation but not in retinal endothelial cells (Al Gwairi et al, 2016). As to the in vivo relevance of these findings, Emoto and colleagues have shown that the mRNA expression of some GAG synthesizing genes increases over 8 weeks in an atherosclerotic mouse model and this increase correlates with increased atherosclerosis in the mice (Anggraeni et al, 2011).…”
Section: Discussionmentioning
confidence: 99%